2018
DOI: 10.3892/mmr.2018.8787
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 inhibits retinal pigment epithelium cell proliferation and migration through regulation of VEGF in rhegmatogenous retinal detachment

Abstract: Rhegmatogenous retinal detachment (RRD) is a disorder of the eye that affects physical and mental health. Retinal pigment epithelium (RPE) is closely associated with RRD, and it is hypothesized that RPE-secreted inflammatory cytokines may induce early pathological changes of RRD and may participate in RPE proliferation and migration. The present study determined a role for interleukin (IL)‑10 as an RPE‑secreted immune regulatory factor that contributes to RRD. A rat RRD model was established and RPE cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Damage to the RPE layer and the underlying choroid may promote infiltration of immune cells and induce retinal microglia and choroidal inflammatory cells to release pro-inflammatory cytokines. A previous study suggested that the anti-inflammatory cytokine IL-10 inhibits RPE cell proliferation and inflammation through the regulation of VEGF in RRD rats ( 39 ), a finding that is consistent with the role of IL-10 in C3a-C3aR- or C5a-C5aR-induced RPE cells. However, the role of C3a-C3aR or C5a-C5aR in the regulation of RPE and immune cells at the retina-choroidal interface remains to be investigated.…”
Section: Discussionsupporting
confidence: 82%
“…Damage to the RPE layer and the underlying choroid may promote infiltration of immune cells and induce retinal microglia and choroidal inflammatory cells to release pro-inflammatory cytokines. A previous study suggested that the anti-inflammatory cytokine IL-10 inhibits RPE cell proliferation and inflammation through the regulation of VEGF in RRD rats ( 39 ), a finding that is consistent with the role of IL-10 in C3a-C3aR- or C5a-C5aR-induced RPE cells. However, the role of C3a-C3aR or C5a-C5aR in the regulation of RPE and immune cells at the retina-choroidal interface remains to be investigated.…”
Section: Discussionsupporting
confidence: 82%
“…The anti-inflammatory role of IL-10 has been shown in a CNV mouse model, where IL-10 deficiency increased inflammation and subsequent intraocular injection enhanced the volume of neovascularization [ 88 ]. Similarly, IL-10 increased the secretion of the proinflammatory cytokine IL-6 through regulation of VEGF production and is implicated in the prevention of the development of rhematogeneous retinal detachment [ 89 ]. Interestingly, our results are consistent with a recent study [ 36 ], revealing that the elevated IL-10 expression levels under LPS-induced inflammatory conditions remained unmodified after application of either N or ND in both cell lines, thus suggesting a protective role of vitamin D against inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper demonstrated that IL-10 inhibited both VEGF expression and proliferation of cultured retinal pigmented epithelial cells isolated from rat eyes following RD. 37 …”
Section: Discussionmentioning
confidence: 99%